Dynamic Thermal Response of Multiple Parallel Cracks in a Half Plane under General Transient Thermal Loading - Mahsa Nourazar; Weilin Yang; Zengtao Chen (Advances in Mathematical Physics)
Understanding the dynamic thermal response of materials is crucial for designing effective thermal protection systems, particularly in extreme thermal environments such as transient thermal loading, extremely low/high temperature, etc. This study investigates the dynamic thermal response of a half plane containing multiple parallel cracks under transient thermal loading using a non-Fourier, hyperbolic heat conduction model. Our findings highlight significant deviations from traditional Fourier models, enhancing the predictive capabilities for designing thermal protection systems in extreme thermal environments. The cracks are modeled as distributions of thermal dislocations, with densities determined through Fourier and Laplace transforms. By solving the resulting singular integral equations, we calculate the temperature gradient intensity factors across multiple scenarios. Additionally, we examine the effects of thermal relaxation time, loading parameters, and crack spacing on the thermal intensity factors, both in transient and steady-state conditions. This research confirms the robustness of the hyperbolic model and its practical implications for thermal analysis in engineering applications.